Forecasts 2.0: a post-pandemic retrospective - Maceri, Sandra Beatriz (2022)
This paper is divided into two main parts to facilitate its exposition. In the first section the forecasting problems will be explained theoretically, where the emphasis will be placed on the fact that they are used despite their recurring failures. In the second section, it will be explained why this problem occurs considering the nature of the extrapolation of past data and some tools provided by behavioral economics.